Factor VIII accelerates proteolytic cleavage of von Willebrand factor by ADAMTS13 - Cao, Wenjing (National Academy of Sciences, 2008)
Proteolytic processing of von Willebrand factor (VWF) by ADAMTS13 metalloproteinase is crucial for normal hemostasis. In vitro, cleavage of VWF by ADAMTS13 is slow even at high shear stress and is typically studied in the presence of denaturants. We now show that, under shear stress and at physiological pH and ionic strength, coagulation factor VIII (FVIII) accelerates, by a factor of ≈10, the rate of specific cleavage at the Tyr(1605)–Met(1606) bond in VWF. Multimer analysis reveals that FVIII preferentially accelerates the cleavage of high-molecular-weight multimers. This rate enhancement is not observed with VWF predenatured with 1.5 M guanidine. The ability of FVIII to enhance VWF cleavage by ADAMTS13 is rapidly lost after pretreatment of FVIII with thrombin. A FVIII derivative lacking most of the B domain behaves equivalently to full-length FVIII. In contrast, a derivative lacking both the B domain and the acidic region a3 that contributes to the high-affinity interaction of FVIII with VWF exhibits a greatly reduced ability to enhance VWF cleavage. Our data suggest that FVIII plays a role in regulating proteolytic processing of VWF by ADAMTS13 under shear stress, which depends on the high-affinity interaction between FVIII and its carrier protein, VWF.